Aortomegaly Causing Nutcracker Syndrome and Pelvic Congestion Syndrome - Rathod, Krantikumar; Sahu, Amit; Popat, Bhavesh; Deshmukh, Hemant (Journal of Clinical Interventional Radiology ISVIR, 2018)
The authors present an uncommon cause of pelvic congestion syndrome (PCS) secondary to anterior nutcracker syndrome, which was caused by aortomegaly. Positional flank and pelvic pain was the only presenting feature with no renal dysfunction. Early and significant decompression of left renal vein (LRV) via left ovarian vein resulted in preserved renal function with symptomatic pelvic varices. Endovascular management by left ovarian vein coiling and LRV stenting was done. They briefly review the etiopathology, imaging, treatment rationale, and management options for nutcracker and PCS.
Keywords: pelvic congestion syndrome; nutcracker syndrome; ovarian vein embolization; renal vein stenting; aortomegaly